Realisation of maqasid al-shariah using value-based intermediation in Islamic banks: acceptance or refusal / Aizurra Haidah Abdul Kadir ... [et al.] - Abdul Kadir, Aizurra Haidah; Syed Alwi, Sharifah Faigah; Abd Halim, Fateha; Mat Nor, Norzanah; Saiful Fikri, Aula Ahmad Hafidh (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2024)
Value-based intermediation (VBI) is a strategy proposed by Bank Negara Malaysia (BNM) as an intermediary tool to deliver the maqasid al-shariah (intended outcomes of Shariah) through practices and product offerings in Islamic banks. However, in reality, VBI has not yet been fully accepted by all Islamic banks in Malaysia even though BNM strongly recommended the implementation. Thus, the objective of this research was to investigate the reason(s) behind the acceptance and refusal of VBI among Islamic Banks in Malaysia. This research used the qualitative research methodology where semi-structured interviews were conducted with the shapers of VBI in Islamic banks or the dedicated officers in corporate social responsibility to gain information on the initiatives. This research showed that the Islamic banks which agree to implement VBI are purely supporting the BNM initiatives. However, the Islamic banks that refused to implement VBI feel that they had adopted a similar concept and strategy as VBI much earlier to achieve maqasid al-shariah. It is recommended that BNM revise and customize VBI in accordance with the Malaysian context and culture for it to be fully accepted by all Islamic banks and be able to avoid any conflicts between the regulator and practitioners.